Readers’ response to a Korean diaspora’s webtoon - Vučkovič, Eva (Asian studies, 2025)
A dailylifetoon is a genre of webtoon that is getting more attention since it reflects the author’s life and readers can easily identify with the storyline. At the same time, it is quickly spreading on social media platforms, thus becoming more accessible. Kore-an diaspora’s dailylifetoon artists portray their own lifestyles, which is seen as a blend of two cultures. This paper examines the webtoon Murrz which depicts the daily life of a Korean-American webtoon artist and her family. Through narrative analysis, we can learn that the author, the main character of the webtoon, adheres to an American way of living, but knows Korean culture and traditions thanks to her parents who migrated to the US as young adults. Her parents are, in the eyes of the webtoon author, “the others”, and therefore she ascribes certain of their behaviours as universal to Koreans. In this regard, the reader’s role becomes important. Readers’ reactions are shown in the comments section of every episode. Most of the readers will relate to the story and share their own experiences in this section. However, some readers will challenge the author’s opinion while commenting that certain situations, which in the author’s view are distinct-ly Korean or Asian, occur in other cultures too. In this article, we investigate how the Korean diaspora is portrayed in the webtoon Murrzand how the artist presents herself and her parents. Further, we discuss the role of the readers of this Korean diaspora webtoon and the impact of the comments section.
Keywords: dailylifetoon; Korean diaspora; korejska diaspora; odziv bralcev; online comments; readers’ response; spletni komentarji; spletni strip; Webtoon